2006
DOI: 10.1021/jf062009b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Phenolic Compounds in Artichoke-Based Dietary Supplements and Pharmaceuticals by High-Performance Liquid Chromatography

Abstract: Dietary supplements are among the most rapidly growing products in the food and personal care market with an estimated worldwide volume exceeding $60 billion. The main problem associated with dietary supplements is their legal classification. Being neither food nor medicine, they often inhabit a gray area between the two, which makes legal regulatory extremely difficult. Thus, a coexistence of products processed from the same botanical source on the same market as dietary supplement or pharmaceutical is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 28 publications
3
28
0
5
Order By: Relevance
“…Our study was meant to identify all possible phytoconstituents with the used experimental setup, and as a consequence 49 and 51 molecules were described in the aqueous and hydro-alcoholic artichoke extracts, respectively. Some of the newly identified compounds were confirmed by standards, while other compounds have already been reported by others [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 63%
“…Our study was meant to identify all possible phytoconstituents with the used experimental setup, and as a consequence 49 and 51 molecules were described in the aqueous and hydro-alcoholic artichoke extracts, respectively. Some of the newly identified compounds were confirmed by standards, while other compounds have already been reported by others [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 63%
“…Despite the many articles reporting the phenolic composition of artichoke hydroalcoholic extracts, 13,15,16,[31][32][33][34][35][36][37][38][39][40] the present work characterizes the phenolic composition in infusions. Moreover, infusion is the most common form to consume this plant and, to our knowledge, this is also the first report presenting results for the whole plant material and not seeds.…”
Section: Flavonoidsmentioning
confidence: 98%
“…The assignments of the different caffeoylquinic, feruloylquinic and p-coumaroylquinic acid isomers were made using the recommended IUPAC numbering system and also the hierarchical keys previously developed by Clifford et al 29,30 Compound 1 ([M -H] − at m/z 353) was identified as 3-Ocaffeoylquinic acid, yielding the base peak at m/z 191 ([quinic acid-H] − ) and the ion at m/z 179 ([caffeic acid-H] − ) with an intensity >63% base peak, characteristic of 3-acylchlorogenic acids as reported by Clifford et al 29,30 Monocaffeoylquinic acids have been largely reported by many authors in different parts of artichoke, such as heads and leaves, 13,15,[31][32][33][34][35][36][37][38] hearts, 16 wastes such as bracts, receptacles and stems from the fruit, 39 juices and pomace, 15,32 and in dietary supplements. 15,37,40 Compound 22 present in milk thistle and artichoke was identified as 3,5-O-dicaffeoylquinic acid based on its fragmentation pattern being similar to that reported by Clifford et al 30 The MS 2 base peak was at m/z 191, but also presented a very high relative abundance at m/z 353, produced by the loss of one of the caffeoyl moieties [M − H-caffeoyl] − , whose subsequent fragmentation yielded the same fragments as 5-Ocaffeoylquinic acid at m/z 191, 179 and 135. Compound 10 (artichoke) was identified as 1,3-O-dicaffeoylquinic acid (cynarin) according to its MS 2 fragmentation and elution characteristics, being the most hydrophilic dicaffeoylquinic acid.…”
Section: Phenolic Acidsmentioning
confidence: 99%
See 2 more Smart Citations